SARS-CoV-2 reliably detected in frozen saliva samples stored up to one year - Frediani, Jennifer K.; McLendon, Kaleb B.; Westbrook, Adrianna; Gillespie, Scott E.; Wood, Anna; Baugh, Tyler J.; O’Sick, William; Roback, John D.; Lam, Wilbur A.; Levy, Joshua M. (PloS one, 2022)
Viability of saliva samples stored for longer than 28 days has not been reported in the literature. The COVID-19 pandemic has spawned new research evaluating various sample types, thus large biobanks have been started. Residual saliva samples from university student surveillance testing were retested on SalivaDirect and compared with original RT-PCR (cycle threshold values) and quantitative antigen values for each month in storage. We conclude that saliva samples stored at -80°C are still viable in detecting SARS-CoV-2 after 12 months of storage, establishing the validity of these samples for future testing.